1996
DOI: 10.1073/pnas.93.24.13931
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous translocations into immunoglobulin heavy chain switch regions in multiple myeloma

Abstract: In multiple myeloma, karyotypic 14q32 translocations have been identified at a variable frequency (10-60% in different studies). In the majority of cases, the partner chromosome has not been identified (14q؉), and in the remaining cases, a diverse array of chromosomal partners has been implicated, with 11q13 being the most common. We developed a comprehensive Southern blot assay to identify and distinguish different kinds of immunoglobulin heavy chain (IgH) switch recombination events. Illegitimate switch reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
250
0
12

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 351 publications
(277 citation statements)
references
References 41 publications
14
250
0
12
Order By: Relevance
“…Some associative correlations have been described, such as non-random chromosomal translocations (Bergsagel et al, 1996;Richelda et al, 1997;Gabrea et al, 1999), but direct demonstration of a role in malignancy for genes near these sites has been elusive. Similarly, mutations in genes frequently observed in other cancers such as p53 and Ras (Portier et al, 1992;Yasuga et al, 1995) have not been consistently observed in myeloma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some associative correlations have been described, such as non-random chromosomal translocations (Bergsagel et al, 1996;Richelda et al, 1997;Gabrea et al, 1999), but direct demonstration of a role in malignancy for genes near these sites has been elusive. Similarly, mutations in genes frequently observed in other cancers such as p53 and Ras (Portier et al, 1992;Yasuga et al, 1995) have not been consistently observed in myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…the Bcl-2 translocation in CML), such lesions have not been identi®ed in MM. During the past few years, a number of translocations have been described in MM such as those involving the immunoglobulin locus and a non-random chromosomal partner (Bergsagel et al, 1996;Richelda et al, 1997). However, the biological signi®cance of such translocations has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal translocations involving the immunoglobulin heavy-chain (IgH) locus on chromosome 14 (14q32) are detected in Ն60% of cases of multiple myeloma (1)(2)(3). Partner chromosome loci and genes participating in these translocations involving the IgH region are largely uncharacterized.…”
mentioning
confidence: 99%
“…MM is frequently associated with chromosome abnormalities, especially translocations involving 14q32 and a variety of other chromosomes, including the short arm of chromosome 4 (Zandecki et al, 1996;Bergsagel et al, 1996). One case of t(4;14) was already described in MM, but with a breakpoint in the 4p16.3 region, implicating the FGFR3 gene, which was shown to be deregulated by juxtaposition to the IgH gene, in this observation (Chesi et al, 1997).…”
Section: A B C D (Ii)mentioning
confidence: 58%